2015
DOI: 10.1097/sla.0000000000001461
|View full text |Cite
|
Sign up to set email alerts
|

Rectovaginal Fistula

Abstract: Our study suggested that aggressive surgical treatment of RVF, including early use of temporary stoma and major procedure in case of failure of previous local treatment, leads to high success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 32 publications
4
59
2
Order By: Relevance
“…3 Despite the high failure rates reported whatever the surgical option chosen, few studies have reported to date an algorithm for the step-up management of RVF. 4 This has ranged from simple seton drainage, fibrin glue, plug insertion, advancement mucosal flaps, sphincteroplasty, biomesh interposition to more complex procedures such as gracilis or Martius muscle interposition or abdominal procedures. 35 The value of the defunctioning stoma in the surgical management of RVF is still debatable; however, it has been reported to improve outcomes in patients who have had a number of failed repairs.…”
Section: Discussionmentioning
confidence: 99%
“…3 Despite the high failure rates reported whatever the surgical option chosen, few studies have reported to date an algorithm for the step-up management of RVF. 4 This has ranged from simple seton drainage, fibrin glue, plug insertion, advancement mucosal flaps, sphincteroplasty, biomesh interposition to more complex procedures such as gracilis or Martius muscle interposition or abdominal procedures. 35 The value of the defunctioning stoma in the surgical management of RVF is still debatable; however, it has been reported to improve outcomes in patients who have had a number of failed repairs.…”
Section: Discussionmentioning
confidence: 99%
“…26 The literature largely consists of patient series in which different techniques are used for different groups of patients according to surgeon preference. 19,27,28 Smoking, 22 obesity, 23 and exposure to pelvic radiation 29 have been associated with significantly higher rates of recurrence.…”
Section: General Considerationsmentioning
confidence: 99%
“…Fibrin glue injection has definitive closure rates in the 10 to 15% range, and thus is typically reserved for patients who cannot tolerate more invasive procedures. 27 A pilot study of autologous fat graft injection to the fistula tract achieved tissue healing in 77% of women after an average of 1.8 procedures, although roughly one-third of their small sample was protected with a diverting stoma. 32 Bioprosthetic plugs have limited data to support their efficacy.…”
Section: Conservative Managementmentioning
confidence: 99%
See 2 more Smart Citations